Novel Survivin Inhibitor YM155 elicits Cytotoxicity in Glioblastoma Cell Lines with Normal or Deficiency DNA-Dependent Protein Kinase Activity - Pei Chun Lai; Shu Huey Chen; Shang Hsien Yang; Chuan Chu Cheng; Ted H. Chiu; Yen Ta Huang (Pediatrics and Neonatology)
Pediatric glioblastoma is a malignant disease with an extremely poor clinical outcome. Patients usually suffer from resistance to radiation therapy, so targeted drug treatment may be a new possibility for glioblastoma therapy. Survivin is also overexpressed in glioblastoma. YM155, a novel small-molecule survivin inhibitor, has not been examined for its use in glioblastoma therapy. Methods: The human glioblastoma cell line M059K, which expresses normal DNA-dependent protein kinase (DNA-PK) activity and is radiation-resistant, and M059J, which is deficient in DNA-PK activity and radiation-sensitive, were used in the study. Cell viability, DNA fragmentation, and the expression of survivin and securin following YM155 treatment were examined using MTT (methylthiazolyldiphenyl-tetrazolium) assay, ELISA assay, and Western blot analysis, respectively. Results: YM155 caused a concentration-dependent cytotoxic effect, inhibiting the cell viability of both M059K and M059J cells by 70% after 48 hours of treatment with 50 nM YM155. The half-maximal inhibitory concentration (IC50) was around 30–35 nM for both cell lines. Apoptosis was determined to have occurred in both cell lines because immunoreactive signals from the DNA fragments in the cytoplasm were increased 24 hours after treatment with 30 nM YM155. The expression of survivin and securin in the M059K cells was greater than that measured in the M059J cells. Treatment with 30 nM YM155, for both 24 and 48 hours, significantly suppressed the expression of survivin and securin in both cell lines. Conclusion: The novel survivin inhibitor YM155 elicits potent cytotoxicity in glioblastoma cells in vitro via DNA-PK-independent mechanisms. YM155 could be used as a new therapeutic agent for the treatment of human glioblastomas.